The Comprehensive Complication Index (CCI) as a Measure of Postoperative Morbidity and Neurological Outcome after Elective Intracranial Surgery - Drexler, Richard; Ricklefs, Franz Lennard; Pantel, Tobias Fabian; Göttsche, Jennifer; Westphal, Manfred; Dührsen, L (Journal of Neurological Surgery Part A: Central European Neurosurgery)
Background: The Comprehensive Complication Index (CCI) is a numerical scale based on the Clavien-Dindo classification (CDC) and both are widely used to assess outcome. However, the CCI had not been described for neurosurgical procedures. Objective: We aimed to investigate the value of the CCI to predict outcome in patients who underwent elective intracranial surgery. Methods: Prospective cohort study including patients who underwent elective intracranial surgery. Complications were graded using CDC, and the CCI was calculated daily. Neurological outcome was assessed using mRS, NANO, NIHSS, and KPS. Results: Of 294 patients who underwent an elective intracranial procedure, 211 (71.8%) patients underwent a craniotomy, while 28 (9.5%) patients had a burr hole procedure and 55 (18.7%) patients a transsphenoidal approach. A higher blood loss was the only significant predictor for a higher CCI (OR 1.09, 95% CI 1.00-1.12, P < 0.01). Patients with a higher CCI had a longer LOS (mean: 5.4 versus 10.9 days, P < 0.01) and ICU stay (mean: 0.8 versus 2.4 days, P < 0.01). Daily CCI revealed a risk for complications after craniotomies until postoperative day (POD) 7. In patients who underwent brain tumor surgery, the resection of meningiomas and metastasis showed a similar developmental course of CCI. A significantly higher CCI was observed in patients who had a neurological deterioration at discharge ( P < 0.01). Conclusion: CCI is a valid scale to measure outcome after intracranial procedures and correlates with neurological outcome. Risk for adverse events after craniotomy is at highest until postoperative day 7.